Impacto geotécnico del diésel en un suelo arcilloso de baja plasticidad (2018)
When oil spills occur in the soil due to gravity and capillary forces, these fluids move vertically and horizontally through the strata; then the following question arises: what happens in the geotechnical properties and the mineralogical composition of a clay soil of low plasticity with the presence of diesel? To answer this question, laboratory tests with controlled variables were required. Thus, the methodology involved taking the samples to the air and then adding water and diesel treatment of 0%, 1%, 3% and 6%, with a one-week exposure time under controlled temperature and humidity conditions. Laboratory tests were done to determine moisture content, specific gravity of solids, Atterberg limits and unconfined compressive strength. The analysis of mineralogy with X-ray diffraction (XRD), dust method, was performed for samples with 0% and 6% diesel treatment. It is important to specify that the effect of temperature on the performance of the tests was evaluated, if the presence of diesel in the soil is unknown, a temperature of 110 ± 5 ° C is used, and if the presence of diesel is known in the soil a temperature of 50 ± 5 ° C is used. The results of the investigation verified the changes in the geotechnical properties and the uncertainty in the estimation of the moisture content and the specific gravity of the solids, but the mineralogical composition was not affected; however, the percentage of micas was reduced.